Subjective return expectations, perceptions, and portfolio choice - Héctor F. Calvo Pardo; Xisco Oliver; Luc Arrondel (Journal of Risk and Financial Management, 2022)
Exploiting a representative sample of the French population by age, wealth, and asset classes, we document novel facts about their expectations and perceptions of stock market returns. Both expectations and perceptions of returns are very dispersed, significantly lower than their data counterparts, and a substantial portion of the variation in the former is explained by dispersion in the latter. Consistent with portfolio choice models under incomplete information, a conditional risk-return trade-off explains the intensive margin, while at the extensive margin, only expected returns matter. Despite accounting for survey measurement error in subjective return expectations, 'muted sensitivities' at both portfolio choice margins obtain, getting consistently (i) bigger when excluding informed non-participants, and (ii) smaller, for inertial and professionally delegated portfolios.
Keywords: 330; subjective expectations; perceptions; portfolio choice; household finance